Molecular transport through 3-hydroxybutyrate co-3-hydroxyhexanoate biopolymer films with dispersed graphene oxide nanoparticles: Gas barrier, structural and mechanical properties. (January 2020) - Mahmood, H.; Pegoretti, A.; Brusa, Roberto S.; Ceccato, R.; Penasa, L.; Tarter, S.; Checchetto, R.
Abstract: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) nanocomposite films containing 0.25 wt % of Graphene Oxide (GO) nanoparticles were prepared by solution-casting and characterized by Differential Scanning Calorimetry (DSC), X-Rays Diffraction (XRD) and Positron Annihilation Lifetime Spectroscopy (PALS). Gas transport properties were analyzed in the 295–343 K interval using CO2, N2, D2 and He. Neat PHBH films showed a semi-crystalline structure with lamellar crystalline domains of 30 ± 1 and 5 ± 1 nm size in the (020) and (002) direction, respectively. GO dispersion increases the PHBH crystalline fraction from 0.28 to 0.60 wt. % without changing the size of crystalline domains and the structure of the PHBH free volume. Nanocomposite films show mechanical properties similar to those of the neat PHBH film but improved gas barrier properties as consequence of the larger number density the of gas- impermeable crystalline domains. Highlights: Graphene oxide/3-hydroxybutyrate co-3-hydroxyhexanoate nanocomposite gas barrier. Graphene Oxide/3-hydroxybutyrate co-3-hydroxyhexanoate free volume structure. Graphene Oxide/3-hydroxybutyrate co-3-hydroxyhexanoate mechanical properties. Measure of CO2, N2, D2, He diffusivity and solubility.